KRISIS GURU PENDAMPING KHUSUS DALAM PEMBELAJARAN ANAK LAMBAT BELAJAR DI SDN WIROPATEN SURAKARTA - Intan Siti Nurfadilah (Prodi PGMI STPI Bina Insan Mulia Yogyakarta, 2025)
This study aims to examine the impact of the limited number of Special Assistant Teachers (GPK) on the learning process of children who are slow to learn in inclusive schools, especially at SDN Wiropaten Surakarta. Children who are slow to learn are one of the categories of Children with Needs (ABK) that require a special learning approach. This study uses a descriptive qualitative approach with a case study method. Data collection techniques are carried out through observation, interviews with GPK, and the review of documentation. The study's results indicate that the limitations of GPK affect pedagogical approaches, including a lack of individual mentoring, a decline in learning motivation, and an increase in the workload for regular teachers. Although schools have tried adaptive strategies, the results are still not optimal. This research not only describes the challenges that exist but also offers strategic solutions as an option to address the GPK crisis.